Synthesis, Quantification, and Characterization of Fatty Acid Amides from In Vitro and In Vivo Sources - Ruidong Ni; Suzeeta Bhandari; Perry R. Mitchell; Gabriela Suarez; Neel B. Patel; Kara Lamb; Kirpal S. Bisht; David J. Merkler (Molecules, 2021)
Fatty acid amides are a diverse family of underappreciated, biologically occurring lipids. Herein, the methods for the chemical synthesis and subsequent characterization of specific members of the fatty acid amide family are described. The synthetically prepared fatty acid amides and those obtained commercially are used as standards for the characterization and quantification of the fatty acid amides produced by biological systems, a fatty acid amidome. The fatty acid amidomes from mouse N18TG2 cells, sheep choroid plexus cells, Drosophila melanogaster, Bombyx mori, Apis mellifera, and Tribolium castaneum are presented.